Gene expression regulatory networks in Trypanosoma brucei: insights into the role of the mRNA-binding proteome - Lueong, Smiths; Mercé, Clémentine; Fischer, Bernd; Hoheisel, Jörg D.; Erben, Esteban D. (Molecular microbiology, 2016)
Control of gene expression at the post-transcriptional level is essential in all organisms, and RNA-binding proteins play critical roles from mRNA synthesis to decay. To fully understand this process, it is necessary to identify the complete set of RNA-binding proteins and the functional consequences of the protein-mRNA interactions. Here, we provide an overview of the proteins that bind to mRNAs and their functions in the pathogenic bloodstream form of Trypanosoma brucei. We describe the production of a small collection of open-reading frames encoding proteins potentially involved in mRNA metabolism. With this ORFeome collection, we used tethering to screen for proteins that play a role in post-transcriptional control. A yeast two-hybrid screen showed that several of the discovered repressors interact with components of the CAF1/NOT1 deadenylation complex. To identify the RNA-binding proteins, we obtained the mRNA-bound proteome. We identified 155 high-confidence candidates, including many not previously annotated as RNA-binding proteins. Twenty seven of these proteins affected reporter expression in the tethering screen. Our study provides novel insights into the potential trypanosome mRNPs composition, architecture and function.